4x-(x+1)=x-(x-5)

Simple and best practice solution for 4x-(x+1)=x-(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(x+1)=x-(x-5) equation:


Simplifying
4x + -1(x + 1) = x + -1(x + -5)

Reorder the terms:
4x + -1(1 + x) = x + -1(x + -5)
4x + (1 * -1 + x * -1) = x + -1(x + -5)
4x + (-1 + -1x) = x + -1(x + -5)

Reorder the terms:
-1 + 4x + -1x = x + -1(x + -5)

Combine like terms: 4x + -1x = 3x
-1 + 3x = x + -1(x + -5)

Reorder the terms:
-1 + 3x = x + -1(-5 + x)
-1 + 3x = x + (-5 * -1 + x * -1)
-1 + 3x = x + (5 + -1x)

Reorder the terms:
-1 + 3x = 5 + x + -1x

Combine like terms: x + -1x = 0
-1 + 3x = 5 + 0
-1 + 3x = 5

Solving
-1 + 3x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 3x = 5 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = 5 + 1
3x = 5 + 1

Combine like terms: 5 + 1 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| 1/4=-x+8/5 | | 6+40=210 | | -1+8y/5=-5/3-y+3y/5 | | 9.5x+3=5.5x+4 | | (4/5)+(2/7)= | | 30z+(27z-5)=-28 | | 17/9= | | 17x-(5x-9)=21 | | -1+y/3=0 | | 3(x)-8=100 | | 6y+3x=15 | | 11y-12/8+3y/5=6y-1/8 | | (2x)^0/-2^4 | | 11+25y+29y=-14+27y-18y | | -5y/4+8/3=0 | | x+8y=38 | | (3r^2+10r-8)(12r^2-4r+3)= | | -9/4+3y+4=-9y-3 | | 2(2x-3)=3(x+6) | | 4(5x+3)=-5(x-2) | | 9k^2+5k+4=0 | | x^2+16x+105=0 | | x+4y=18 | | 62=9x+8 | | 12(5+6m)+16=-90 | | -40y+8x+48=0 | | 4z/5-7/3=2z/3-2z/3 | | -40x+8y+48=0 | | (x+6)(x+6)(x-8)(4x-5)=0 | | 1.2x+4(0.4x+8)=24 | | x^2-4x+4=o | | -(11y+8)-20y-25y=21 |

Equations solver categories